A simplified procedure for predicting the soil amplification factor based on the strain compatible period. Issue 144 (May 2021) - Yaghmaei-Sabegh, Saman; Yilmaz, Emir Misbah
Abstract: This paper proposed a simplified procedure for predicting the amplification factor based on a new empirical model for estimating the site period considering nonlinear strain range of soil. The analysis results suggested the depth to bedrock of the soil profile affects the site period at certain shaking intensity levels. Considering this finding, we first proposed a new empirical model to estimate the site period by propagating 78 input motions through 119 soil profiles. A statistical method confirmed the accuracy of the proposed empirical method, which represents the effect of both dynamic properties of soil and input motion features on site response. We then presented a simplified procedure for predicting the amplification factor by taking to account the site period shift and soil nonlinear behavior due to the interaction of damping increase and the resonance controlling effect. Finally, the accuracy of the simplified procedure results in predicting the amplification factor was evaluated by considering the equivalent linear and nonlinear approaches. The results revealed that the simplified model captures the trends of equivalent linear site response analyze in predicting the amplification factor with acceptable accuracy. Highlights: New empirical method is proposed to calculate the strain compatible period. A simplified procedure is proposed to predict the amplification factor based on the strain compatible period. The depth to bedrock of the soil profile affects the site period at certain shaking intensity levels.